Analisis Empiris Terhadap Determinan Praktik Pengungkapan Modal Intelektual pada Perusahaan Publik BEJ - Purnomosidhi, Bambang (TEMA, 2005)
In the â€˜new economyâ€™ era, ideas, practices, and innovations that arise from the creation of intellectual capital have become a pre-eminent economic resources and the basis for competitive advantage. Yet, traditional accounting practices does not provide for the identification and measurement of these â€œnewâ€ intangibles in companies. A a result, that traditional financial reporting is inadequate in meeting with the information needs of stakeholders. This study examines voluntary intellectual capital disclosure provided by listed Indonesian companies in annual reports from the year2001, 2002, and 2003, both qualitatively and quantitatively. Additionally, the study also aims to answer what are factors that influence different voluntary reporting behavior among publicly listed companies in Indonesia This study adopts the framework of Karl Erik Sveiby which classified intellectual capital as internal capital, external capital, and employee competence. A content analysis of 84 copies of annual reports was carried out. The study indicates that the frequencies of voluntary disclosure of intellectual capital in company report are high qualitatively, but not quantitatively, and focus more on external capital. In addition, the key component of intellectual capital are apparently poorly understood, inefficiently managed, and finally they are not reported within a consistent framework. Regarding the factors that can explain different voluntary reporting practices, finding suggest that size, leverage and intellectual capital performance found to have an influence on the amount of intellectual capital disclosure. However, results suggest that when a companyâ€™s intellectual capital performance is too high there is a negative impact on the amount of intellectual capital disclosure. The negative association may support the suggestion companies reduce intellectual capital disclosure when intellectual capital is above a perceived ceiling level for fear of losing a competitive advantage. Other factors, such as industry type, listing status, and financial performance were found not to have an influence on the amount of intellectual capital disclosure. Keywords: Intellectual capital, voluntary disclosure, competitive advantage